2012
DOI: 10.1007/s10719-012-9437-7
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly glycosylated MUC1 is expressed on the surface of breast cancer cells and a target for antibody-dependent cell-mediated cytotoxicity

Abstract: Protein glycosylation often changes during cancer development, resulting in the expression of cancer-associated carbohydrate antigens. In particular mucins such as MUC1 are subject to these changes. We previously identified an immunodominant Tn-MUC1 (GalNAc-α-MUC1) cancer-specific epitope not covered by immunological tolerance in MUC1 humanized mice and man. The objective of this study was to determine if mouse antibodies to this Tn-MUC1 epitope induce antibody-dependent cellular cytotoxicity (ADCC) pivotal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 49 publications
1
53
0
Order By: Relevance
“…22 Besides findings of elevated MUC1 levels in physiological conditions (e.g., pregnancy, lactation period), 12,23 MUC1 is believed to play a pivotal role in the adhesion processes of cells (cell-cell and cell-extracellular matrix interactions), failure of immune recognition and in immunosuppressive effects. 24 In this context, the positive prognostic impact of MUC1-specific immunoglobulin serum levels in breast cancer patients was associated with the function of MUC1 as a ligand for the intercellular adhesion molecule 1 (ICAM-1) as well as for E-selectin.…”
Section: Discussionmentioning
confidence: 99%
“…22 Besides findings of elevated MUC1 levels in physiological conditions (e.g., pregnancy, lactation period), 12,23 MUC1 is believed to play a pivotal role in the adhesion processes of cells (cell-cell and cell-extracellular matrix interactions), failure of immune recognition and in immunosuppressive effects. 24 In this context, the positive prognostic impact of MUC1-specific immunoglobulin serum levels in breast cancer patients was associated with the function of MUC1 as a ligand for the intercellular adhesion molecule 1 (ICAM-1) as well as for E-selectin.…”
Section: Discussionmentioning
confidence: 99%
“…While MUC1 expression is limited to the apical surface of most ductal epithelium, in metastatic disease, MUC1 is overexpressed and becomes localized throughout the cell. 7 This has perhaps been most intensively studied in breast cancer, in which MUC1 expression has been evaluated clinically at the level of immunohistochemistry, 8,9 RNA, 10 shed MUC1 in sera, expression on circulating tumor cells (discussed below) and biochemically, 11 and has correlated with poor disease-free and overall survival, as well as axillary node metastases. 9 MUC1 expression is seen in all subtypes of breast cancer, including luminal, HER2 + studies in metastatic breast, colorectal, gall bladder, non-small cell lung and gastric cancer, using KL-6, discovered that MUC1 expression at the circumference of the plasma membrane and/or in the cytoplasm frequently correlated with deep invasion, lymph node or liver metastasis and decreased five-year survival.…”
Section: Muc1 Expression Correlates With Metastasismentioning
confidence: 99%
“…MUC1 expression correlated with invasion and metastasisandpoorsurvivalinsomecancers.Itwas reported that MUC1 was overexpressed in breast cancer,andwasabsentorexpressedatalowlevelin normalmammarygland.MUC1mightbeapoten-tialtargetinbreastcancerimmunotherapy [10,11]. In gastric cancer, MUC1 was not only expressed in metastatic disease, but also found to be highly expressedinprimarytumor,indicatingthatitmightbe promoting initial spread [12,13].…”
Section: Discussionmentioning
confidence: 99%